Social insurance and allied services : memorandum on the Beveridge Report
1943-02-10 1943 1940s 24 pages 10. TABLE "C". 1938 1945 1965 Under "Beveridge" Increase + or Decrease - in 1965 as against under existing law. Under Existing Law. Under "Beveridge" £ Mill. £ Mill. £ Mill. £ Mill. £ Mill. (A) Paid without proof of Want 207 (61%) 258 (60%) 650 (93%) 826 (96%) + 568 (B) Paid on proof of Want 135 (39%) 174 (40%) 47 (7%) 32 (4%) - 142 342(100%) 432(100%) 697(100%) 858(100%) + 426 (32) The fact that payment is made "without proof of Want" does not necessarily mean that the recipient may not in fact be in want, and the above Table is not therefore put forward as drawing a line between those who are not in want and those who are in want. There are, however, certain inferences which emerge from the Table. (33) It will be seen that by 1965 the payments made "without proof of Want" would amount to 96% of the total cost - as compared with 60% under the existing law - and that the increase in the amount to be paid "without proof of Want" would be £568. It has to be borne in mind, however, that in 1965 there would be paid "on proof of Want" £142 millions less than today, but, even after deducting that sum, there is still an increased expenditure of £426 millions unaccounted for. (34) It is therefore important, in our view, to examine how much of that £426 millions paid "without proof of Want" would, under the "Beveridge" plan be devoted to the plan's first objective of the Abolition of Want, and how far it would be devoted to the providing of Allowances, Benefits, Services and Grants, to those who are not in Want. Unfortunately, not much Information is contained in the Report on which to arrive at any precise estimate on that point. Sir William/ 200/B/3/2/C216/5/50